Strategi Guru dalam Menjelaskan Materi guna Meningkatkan Nilai Mata Pelajaran Siswa di SD Inpres Taratara 1 - Romi Mesra; Paulus Robert Tuerah; Muhammad Fajar Hidayat (Ideas Publishing, 2023)
The ability to explain material to students is one of the basic teaching skills that must be mastered by a teacher. Teachers must be familiar with various learning strategies in order to choose the one that is most effective for teaching their students. The purpose of this research is to find out how the teacher s strategy in explaining the material in order to increase the value of student subjects. This study used qualitative research methods. The results of this study indicate that the teachers basic teaching skills in explaining there are several strategies that are carried out, namely the teacher explains by attracting students attention, the teacher behaves humorously and is not rigid in starting learning, the teacher explains the learning objectives, the teacher carries out learning activities outdoors, the teacher changes the learning atmosphere, the teacher applies various learning models and methods. It is hoped that the results of this research can be useful for the academic world and of course also for society and can be used as relevant reference material.